Synthesis, crystal structures and photoluminescent properties of two Cd(II)/Zn(II) coordination polymers with rarely 8-/2-fold interpenetrated based on 4, 4′-stilbenedicarboxylic acid and imidazole ligands. Issue 4 (16th February 2017) - Fan, Chuan-Bin; Meng, Xiang-Min; Fan, Yu-Hua; Cui, Lian-Sheng; Zhang, Xia; Bi, Cai-Feng
Abstract: Two coordination polymers, [Cd(sbdc)(bmib)]n (1 ) and [Zn(sbdc)(tib)]·0.5H2 On (2 ) (H2 sbdc = 4, 4′-stilbenedicarboxylic, bmib = 1, 4-bis(2-methylimidazol-1-yl)butane, tib = 1, 3, 5-tris(1-imidazolyl)benzene), have been synthesized under solvothermal conditions, characterized by elemental analysis, infrared spectra, thermogravimetric analysis, and single-crystal X-ray diffraction. Single-crystal X-ray diffraction analysis reveals that1 and2 show 8-fold and 2-fold interpenetrating 3-D frameworks, respectively. Complexes1 and2 display a 4-connected (6 6 )sqc6 and a 4-connected (4 4 ·6 2 )sql topology, respectively. Photoluminescent and thermal properties of1 and2 have also been investigated. Abstract :